An edition of wills proved in the Prerogative Court of Canterbury, 4 November-31 November, 1549: thesis presented in fulfillment of the requirements for the degree of Master of Arts at Massey University - Plimmer, Rosalind (Massey University, 1985)
This edition of wills is a transcription of forty-five consecutive testaments in the Populwell Register 1 , probated in the Prerogative Court of Canterbury during the month of November 1 549. Preserved on microfilm, this register has been classified PROB 11 /32. The register is uniformly written in the sixteenth century 'secretary' hand. As the dates of probate run consecutively through the first twenty-six testaments, 4 November to 19 November, then make a rather muddled order through the remaining nineteen testaments, it is probable that the wills were not written into the register at the time of probate but collated and written up at a later date. Throughout this thesis my intention has been to remain as close to the manuscript as possible, retaining the manner and style of the English language during the sixteenth century. All contractions commonly found in the Tudor 'secretary' hand of the manuscript have been expanded in this text, and underlined to indicate this to the reader. The punctuation has been modernized from 11/ 11 , II / If and ft ft to commas and full stops to ease the understanding of the transcript.
Keywords: Wills -- History; Church of England. Province of Canterbury.; Prerogative Court